Pengembangan Media Pembelajaran Interaktif Berbasis Website Zep Quiz pada Mata Pelajaran Sanitasi dan Hygiene Kecantikan - Siti Muthia Anggaraini S. Yantu; Anik Maghfiroh; Ade Novi Nurul Ihsani; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The learning process in the subject of Sanitation and Beauty Hygiene at SMK Tamansiswa Kudus tends to be passive because it is dominated by lecture methods, which has an impact on low student interest and learning outcomes. This study aims to develop an interactive learning media based on the Zep Quiz website and test its feasibility, effectiveness, and practicality to overcome these problems. This type of research is Research and Development (RnD) by applying the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the research trial were 16 students of grade X of the Beauty and SPA Study Program. Data collection techniques included observation, expert validation sheets, learning outcome tests (pretest and posttest), and student response questionnaires. The results showed that the learning media obtained a very feasible level of feasibility with an expert validation score of 88.67%. The effectiveness test showed an effective category (77.04%) as indicated by an increase in the average student score from 46.5 in the pretest to 87.75 in the posttest. The conclusion of this study is that the Zep Quiz-based learning media is feasible, effective, and practical for improving students' theoretical understanding and learning interest in Sanitation and Beauty Hygiene in vocational high schools.